Prediabetes and risk of diabetes and associated complications: impaired fasting glucose versus impaired glucose tolerance: does it matter?. Issue 5 (September 2016) - Abdul-Ghani, Muhammad; DeFronzo, Ralph A.; Jayyousi, Amin
Abstract : Purpose of review: The purpose of this review is to summarize the distinct metabolic and pathophysiologic phenotype of impaired fasting glucose (IFG) and impaired glucose tolerance (IGT) and the subsequent clinical implications with regard to future type 2 diabetes mellitus (T2DM) and cardiovascular risk. Recent findings: Both IFG and IGT manifest the two core defects of T2DM, that is, insulin resistance and β-cell dysfunction. However, the site of insulin resistance and shape of β-cell dysfunction differ. These distinct metabolic and pathophysiologic phenotypes explain the greater cardiovascular disease (CVD) risk associated with an increase in the 2-h plasma glucose concentration, that is, IGT compared with an increase in the fasting plasma glucose (FPG) concentration, that is, IFG. Moreover, the increase in future T2DM risk in IFG study participants is, at least in part, explained by the strong correlation between the increase in FPG and the increase in 2-h plasma glucose concentration. Summary: Last, recent studies have reported the presence of diabetic microvascular complications, that is, retinopathy and neuropathy, at the IGT stage. Thus, a glucose load (e.g. oral glucose tolerance test) is required in study participants with elevated FPG concentration to accurately assess their future risk for T2DM, as well as their risk for CVD to identify the subgroup of IFG who are at greater risk and subject them to an intervention program to decrease their future T2DM and CVD risk.